Comparative study of indoor-outdoor exposure against volatile organic compounds in South and Middle America - Herbarth, O. (2008)
Volatile organic compounds (VOCs) play an important role in indoor and outdoor air pollutants. In the present study, samples were analyzed from indoor (schools and houses) and outdoor air in urban, industrial, semi-rural and residential areas from Argentina (La Plata region) and Mexico (Mexico City region) to consider VOC exposure in different types of environments. VOCs were sampled using a passive sampling method with passive 3M monitors. Samples were extracted with CS2 and analyzed by GC/MS detectors. The results show significant differences in concentration and distribution between indoor and outdoor samples, depending on the study area. Most VOCs predominantly originated indoors influenced by local outdoor emissions (traffic and industry).